Trans(per)Forming Nina Arsenault : an unreasonable body of work - Rudakoff, Judith D., 1953- (Intellect, 2012)
"After sixty surgeries at a cost of almost 200,000 to feminize and beautify her originally male body, transgendered Canadian artist Nina Arsenault has created a body of work emanating from her experiences that includes photographs, videos disseminated online, a website, a blog, several social networking presentation sites, stage plays, print media writing, and performance of the body in both celebrity appearances and daily public life"--provided by publisher.